ESSENCE-Q – used as a screening tool for neurodevelopmental problems in public health checkups for young children in south Japan - Hatakenaka Y (Dove Medical Press, 2017)
Yuhei Hatakenaka,1,2 Hitoshi Ninomiya,3 Eva Billstedt,2 Elisabeth Fernell,2 Christopher Gillberg2 1Kochi Gillberg Neuropsychiatry Centre, Kochi Prefectural Medical and Welfare Center, Kochi, Japan; 2Gillberg Neuropsychiatry Centre, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 3Integrated Centre for Advanced Medical Technologies, Kochi University Medical School, Kochi, Japan Background: Screening for developmental disorders is an important task for Child Health Care. The concept of ESSENCE (early symptomatic syndromes eliciting neurodevelopmental clinical examinations) was created to cover all types of early developmental disorders and the ESSENCE-Questionnaire (ESSENCE-Q containing 12 questions with possible total scores ranging from 0 to 22) was developed as a tool for early detection of these disorders. The aim of this study was to perform a validation study in a public health situation in Japan.Methods: The psychometric properties of the ESSENCE-Q, completed by mothers, public health nurses (PHNs), and psychologists at 18-month (n=143 children) and 36-month (n=149 children) checkups were evaluated in a small city of Japan. Results were validated against clinical ESSENCE diagnoses. Receiver operating characteristic curves were generated and compared by using the area under the curve (AUC). Optimal cutoff values were explored.Results: At the 18-month checkup, AUC by mothers was 0.72, by PHNs 0.86, and by psychologists 0.82. An optimal cutoff was 3 with a high negative predictive value (NPV). At the 36-month checkup, AUC by mothers was 0.57, by PHNs 0.82, and by psychologists 0.87. Optimal cutoff was 2 with high NPV.Conclusion: The ESSENCE-Q completed by PHNs and psychologists had good diagnostic validity. The results suggested that almost all children scoring under cutoff would not have any ESSENCE problems/diagnoses. Keywords: ESSENCE, questionnaire, public health nurse, receiver operating characteristic, ROC, area under the curve, AUC, optimal cutoff, negative predictive value, NPV